Ajaran Budi Pekerti dalam Iluminasi Naskah Babad Kartasura - Sukawati - Venny Indria Ekowati; Sri Hertanti Wulan; Aran Handoko; Nur Hanifah Insani (Masyarakat Pernaskahan Nusantara (The Indonesian Association for Nusantara Manuscripts, Manassa), 2018)
This research aims to identify and anylize character building that include in the illumination the text of Babad Kartasura-Sokawati. The data collected through content anylisis and photography. Overall, illuminations picture that include in the text of Babad Kartasura-Sokawati contain character building of Javanese people. There are six character buildings that appear from the illumination, there are: 1) leadership value that appeared from the pictures of eagle, peacock, deer, kingdom’s flag, weapons, bridge fence, star, sun, mountain, river, forest, khandhil (oil lantern), leaf lined, lotus, and sunflower; 2) respect and honorable value that appeared from the pictures of eagle, peacock, kingdom’s flag, dhampar (the king’s seat), leaf lined, and sunflower; 3) value of the perfection of life that appeared from the pictures of khandhil (oil lantern), sunflower, and vines; 4) devotion value that appeared from the pictures of the star and the moon; 5) value to achieve peacefully of the inner and outer that appeared from the pictures of water waves; and 6) noble character value that appeared from the pictures of songsong (gold umbrella), leaf lined, rose, and sunflower. — Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis ajaran budi pekerti di dalam iluminasi teks Babad Kartasura-Sokawati. Data dikumpulkan dengan analisis isi dan dokumentasi. Secara keseluruhan gambar iluminasi yang terdapat dalam teks Babad Kartasura-Sokawati memuat ajaran budi pekerti yang selaras dengan kehidupan masyarakat Jawa. Terdapat enam ajaran budi pekerti yang terdapat dalam gambar iluminasi, yaitu: 1) ajaran tentang kepemimpinan yang tersurat dari gambar burung garuda, burung merak, kijang, umbul-umbul, senjata, pagar jembatan, bintang, matahari, gunung, sungai, hutan, khandhil (lentera minyak), daun yang berjajar, bunga teratai, dan bunga matahari; 2) ajaran saling menghormati dan menghargai yang tersurat dari gambar burung garuda, burung merak, umbul-umbul, pagar jembatan, dhampar (kursi raja), daun yang berjajar, serta bunga mawar; 3) ajaran tentang kesempurnaan hidup yang tersurat dari gambar khandhil (lentera minyak), bunga matahari, dan tumbuhan sulur; 4) ajaran ketaqwaan yang terdapat dalam gambar bintang dan bulan sabit; 5) ajaran untuk meraih ketentraman lahir dan batin yang tampak pada gambar gelombang air; serta 6) ajaran berpekerti luhur yang tampak dari gambar songsong (payung emas), daun yang berjajar, bunga mawar, dan bunga matahari.